Management of agroecological soy varieties, agronomic characteristics and yield (Research, Society and Development, 2021)
The demand for agroecological grains is increasing and this generates a demand for adapted varieties as producing regions of these grains. Thus, this study aimed to evaluate the agronomic characteristics, the productivity of agroecological soybean varieties in the agricultural year 2020/2021; as well as presenting reports on fertility management, spontaneous plant control, pests and diseases of these varieties. The different varieties were cultivated in a Eutroferric Red Latosol. Record the plant height, stem diameter, height of insertion of the first pod, number of nodes, total number of pods, total grains per plant, plant population, weight of a thousand grains, bed plant index and yield. After harvesting, the number and area of ​​damage caused by stink bugs were evaluated. The varieties with the highest productivity were: BRS 525 cultivated in the two stands and BRS 539, BRS 391 and BR 16 6013 cultivated in the Kathounian stand with an average yield of 3178 kg ha-1. However, the harvested grains present a lot of damage caused by the bugs, which reduces their quality. The results demonstrate that the management adopted for agroecological soybean cultivation is adequate, but update improvements such as the management of stink bugs and that these results are in great demand for the choice of soybean cultivars to be cultivated in an agroecological system in the region.